2008
DOI: 10.1007/s00106-008-1670-9
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der CT-Diagnostik vor Revisions-Stapedotomien

Abstract: BACKGROUND: Stapedectomy and, more recently, stapedotomy have been widely accepted as the primary surgical techniques to improve conductive hearing in patients suffering from otosclerosis. Unsuccessful outcomes are infrequent, but revision surgery may become necessary. We have analyzed the value of computed tomography (CT) scanning following unsuccessful stapes surgery. PATIENTS AND METHODS: In a total of 37 CT scans, the depth of insertion, angle between prosthesis and footplate, location of prosthesis within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Postoperative radiological control is helpful to improve the quality of the surgical approach, to monitor the audiological outcome, and to be able to decide which revisions may be required after cochlear implantation and stapes surgery [1012]. Although the radiological resolution has improved and increased with the advent of new technologies (e.g., 64-MSCT, flat-panel tomography, and digital volume tomography), it has been shown that there is a difference between temporal bone measurements and radiological estimations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative radiological control is helpful to improve the quality of the surgical approach, to monitor the audiological outcome, and to be able to decide which revisions may be required after cochlear implantation and stapes surgery [1012]. Although the radiological resolution has improved and increased with the advent of new technologies (e.g., 64-MSCT, flat-panel tomography, and digital volume tomography), it has been shown that there is a difference between temporal bone measurements and radiological estimations.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative, radiological evaluation of the position of otological implants is a useful tool for quality control, for example, in cochlear implantation [10] and stapes surgery [11, 12]. It is important for the clinical outcome, for making decisions about surgical revisions, and for optimizing the surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…HRCT of the temporal bone is a useful tool in the decision-making process concerning stapes revision [147], especially if conductive hearing loss persists after primary surgery. In these cases, HRCT is able to detect additional pathologies of the temporal bone which may account for the persistent hearing loss, e.g.…”
Section: Selected Surgical Proceduresmentioning
confidence: 99%